Legal Settlement of Land Disputes at the Bone Regency National Land Office - Alwi Jaya; Gustika Sandra; Tarmizi (Publikasi Indonesia, 2021)
The purpose of this research is to find out the procedures used by the Bone Regency National Land Agency in resolving land disputes as an implementation of one of the functions of the Regency National Land Agency. Bone and what mechanisms the National Land Agency of Bone Regency takes in resolving land disputes. Dispute resolution does not always have to be done in court, but can be done independently between them based on deliberation and consensus, and the most important thing is that there is a sense of kinship, because this method does not damage the kinship relationship between them . In this research the author uses a conceptual approach method, namely the conceptual approach is an approach that departs from views and doctrines that have been developed in legal science and will give research to understandings, legal concepts and legal principles that are relevant to the issue at hand . Therefore, this research is intended to describe land dispute resolution procedures at the Bone Regency Land Office. This activity provides progressive benefits and helps the community understand Legal Dispute Settlement over Land at the Bone Regency Land Office in accordance with applicable law and broadens the community's insight so that they are wise in resolving land disputes as an effort to avoid disputes.